The complete Mediterranean cookbook : 500 vibrant, kitchen-tested recipes for living and eating well every day (Brookline, MA : America's Test Kitchen, 2016)
Bring the Mediterranean--from Italy and Greece, to Morocco and Egypt, to Turkey and Lebanon--into your kitchen with more than 500 fresh, flavorful recipes. This comprehensive cookbook translates the famously healthy Mediterranean diet for home cooks with a wide range of creative recipes, many fast enough to be made on a weeknight, using ingredients available at your local supermarket. The structure of the book follows the guidelines of the Mediterranean Diet Pyramid. You'll find large chapters devoted to Beans and to Vegetables, the Seafood Chapter is larger than Poultry and Meat, and the Fruits and Sweets chapter, while shorter, is packed with recipes you can truly feel good eating. Recipes include Spiced Baked Rice with Potatoes and Fennel, Tagliatelle with Artichokes and Parmesan, Orzo with Shrimp, Feta, and Lemon, Za'atar-Rubbed Chicken, Greek-Style Braised Pork with Leeks, and Orange Polenta Cake.
1.Meze, antipasti, tapas, and other small plates -- 2.Soups -- 3.Salads -- 4.Rice and grains -- 5.Pasta and couscous -- 6.Beans -- 7.Vegetables -- 8.Seafood -- 9.Poultry -- 10.Eggs -- 11.Breads, flatbreads, pizzas and more -- 12.Fruit and sweets -- Nutirional information for our recipes -- Conversions and equivalents.
Includes index.
Keywords: COOKING -- MEDITERRANEAN